The granulation tissue preservation technique in regenerative periodontal surgery-a randomized controlled clinical trial - Knut Adam; Hüsamettin Günay; Bernhard Vaske; Marco Flohr; Ingmar Staufenbiel (Wiley, 2022)
Abstract Objectives To investigate if the application of the granulation tissue preservation technique (GTPT) in regenerative therapy of infrabony periodontal defects results in more clinical attachment level (CAL) gain and more radiographic bone gain (RBG) than the conventional resective approach 12 months after surgery. Materials and methods Forty patients exhibiting at least one infrabony defect with a probing pocket depth (PPD) ≥6 mm and a radiographic infrabony component (INFRAX‐ray) ≥3 mm were randomly treated with the GTPT (test group) or the double‐flap approach with resection of the defect‐filling granulation tissue (control group). Enamel matrix derivatives were applied in both groups. Clinical and radiographic parameters were recorded at baseline (t0), 6 months (t1), and 12 months (t2) after surgery. The primary outcome variable was CAL gain between t0 and t2. Results When all patients were considered, ΔCALt0-t2 did not differ significantly between the two groups (p = .160). Significant PPD reduction (test group: 4.38 ± 1.36 mm; control group: 4.06 ± 2.38 mm), CAL gain (test group: 3.75 ± 1.24 mm; control group: 2.88 ± 2.09 mm), and RBG (test group: 3.06 ± 1.74 mm; control group: 3.27 ± 2.19 mm) were achieved at t2 in both groups. Using multivariate linear regression, PPDt0 and group were identified as variables with the greatest influence on ΔCALt0-t2. PPDt0 and INFRAX‐ray were identified as variables with the greatest influence on RBGt0-t2. Patients with a defect angle >22° showed significantly more CAL gain in the test group (t0-t1: 3.08 ± 1.38 mm; t0-t2: 3.62 ± 0.96 mm) than in the control group (t0-t1: 1.77 ± 1.54 mm; t0-t2: 2.18 ± 1.83 mm). Conclusions Regarding all patients, the study failed to show significant differences between the test and control groups. However, the GTPT appears to lead to more CAL gain in noncontaining infrabony defects.